Analysis of Data Communication Networks for VTS Surabaya in Class I Type A Navigation District Tanjung Perak - Prima Yudha Yudianto; Shofa Dai Robbi; Muhammad Dahri (Jurnal Indonesia Sosial Sains, 2024)
A reliable data communication network is essential in supporting Vessel Traffic Service (VTS) operations, especially in managing vessel traffic in the Class I Navigation District of Tanjung Perak, Surabaya. However, challenges such as network reliability, bandwidth capacity, and potential interference are still obstacles in ensuring efficient operations. This research aims to analyze the condition of the data communication network at the Tanjung Perak Class I Navigation District VTS, focusing on the technology used, its performance, and the obstacles faced. This research uses a qualitative descriptive approach, with data collected through direct observation, interviews with VTS operators, and analysis of related documents. The results show that the communication network at VTS uses Very High Frequency (VHF) frequency-based radio communication technology to support operations, such as digital maps of ship traffic and Automatic Identification System (AIS) systems. In conclusion, the data communication network at the Tanjung Perak Class I Navigation District VTS has met basic operational needs, but still requires further development in terms of technology and infrastructure to improve its efficiency and reliability. This research provides recommendations for the integration of advanced technology, infrastructure improvement, and human resource training to optimize the performance of the communication network.